Analysis Of Service Quality On Return Visit Interest At Beauty Clinic At WTC Sudirman Skin Clinic, South Jakarta - Selica Erlindi; Mustamin, Mustamin; Amir Mahmud; Andi Zulkifli Abdullah; Zainuddin, Zainuddin (Jurnal EduHealth, 2024)
This study aims to analyze the influence of service quality on patients' revisit intentions at Clinic Skin WTC Sudirman, Jakarta Selatan. With increasing competition in the beauty industry, service quality has become a crucial factor in retaining and attracting patients. This study is motivated by the importance of service elements, such as reliability, tangibles, responsiveness, assurance, and empathy, in building patient loyalty. The method used in this research is quantitative with a cross-sectional design. Data were collected through questionnaires from 80 respondents selected randomly. The findings reveal that all dimensions of service quality significantly influence revisit intentions, with assurance being the most dominant dimension. The study concludes that optimal service quality can increase revisit intentions. The main recommendation is for Clinic Skin management to enhance assurance aspects and provide continuous staff training to maintain patient satisfaction.